2013
DOI: 10.1371/journal.pone.0064847
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrolysin Ameloriates Cognitive Deficits in Type III Diabetic Rats

Abstract: Cerebrolysin (CBL), a mixture of several active peptide fragments and neurotrophic factors including brain-derived neurotrophic factor (BDNF), is currently used in the management of cognitive alterations in patients with dementia. Since Cognitive decline as well as increased dementia are strongly associated with diabetes and previous studies addressed the protective effect of BDNF in metabolic syndrome and type 2 diabetes; hence this work aimed to evaluate the potential neuroprotective effect of CBL in modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 58 publications
3
28
0
5
Order By: Relevance
“…Both neurotrophins (BDNF and NGF) are implicated with spinogenesis and increase dendritic arbor (Adams et al, ; Kolarow, et al, ). According to our results, a recent report has demonstrated that Cbl may reduce high levels of NO and increase low levels of glutamate content in the hippocampus of streptozotocin‐induced hyperglycemia, an animal model of diabetes mellitus (Georgy et al, ). Finally, our recent reports in aged animals demonstrated that Cbl increases the dendritic arbor and dendritic spine density of the pyramidal neurons of the CA1 and DG of the dorsal hippocampus and layer 3 and 5 of the PFC (Alcantara‐Gonzalez et al, ; Juárez et al, ).…”
Section: Discussionmentioning
confidence: 87%
“…Both neurotrophins (BDNF and NGF) are implicated with spinogenesis and increase dendritic arbor (Adams et al, ; Kolarow, et al, ). According to our results, a recent report has demonstrated that Cbl may reduce high levels of NO and increase low levels of glutamate content in the hippocampus of streptozotocin‐induced hyperglycemia, an animal model of diabetes mellitus (Georgy et al, ). Finally, our recent reports in aged animals demonstrated that Cbl increases the dendritic arbor and dendritic spine density of the pyramidal neurons of the CA1 and DG of the dorsal hippocampus and layer 3 and 5 of the PFC (Alcantara‐Gonzalez et al, ; Juárez et al, ).…”
Section: Discussionmentioning
confidence: 87%
“…Currently, as mentioned before, patients with DM who have exhibited a chronic increase in glycemic blood levels (hyperglycemia) have shown changes in the brain, such as a reduced size of the PFC and the hippocampus with cognitive deficits in declarative memory (Bruehl et al, ; Kerti et al, ; van Bloemendaal et al, ; Yang et al, ; Zhang et al, ; Zhou et al, ). Moreover, recent reports in animal models with DM‐induced by streptozotocin have shown that continuous hyperglycemia leads to damage at the neuronal level (Georgy, et al, ; Lazcano et al, ; Martinez‐Tellez et al, ; Sanchez‐Vega et al, ; Shingo et al, ). High levels of glycemia may produce dendritic atrophy with a reduced number of dendritic spines at the level of pyramidal neurons of the PFC and the hippocampus in the rats (Brocca et al, ; Joghataie et al, ; Lazcano et al, ; Martinez‐Tellez et al, ; Shingo et al, ; Xiang et al, ) and mice (Beauquis et al, ; Malone et al, ; Sanchez‐Vega et al, ; Taylor et al, ) (see Table ).…”
Section: Neural Transmission In Animal Model Of Dmmentioning
confidence: 99%
“…Церебролизин потенцирует когнитивную функцию на моделях сахарного диабета, уменьшая уровень провоспали-тельного фактора (фактор некроза опухоли α), повышая уровень инсулиноподобного гормона роста (IGF-1), серо-тонина и оказывая антиоксидантное действие на нейроны головного мозга [35].…”
Section: таблица 2 а к т и в н о с т ь с од в р а з л и ч н ы х н е unclassified
“…Под влиянием церебролизина улучшается восстанов-ление когнитивных способностей после легкой ЧМТ, в ча-стности за счет стимулирования ангиогенеза и быстрого восстановления поврежденной нейрональной сети [35]. Улучшение неврологического состояния при использова-нии церебролизина после экспериментального сотрясения мозга сопровождалось восстановлением целостности аксо-нов в полосатом теле.…”
Section: таблица 2 а к т и в н о с т ь с од в р а з л и ч н ы х н е unclassified